SYSTEM-DRIVEN (UN) FRAUD: TAFSIR APARATUR TERHADAP âSISI GELAPâ PENGELOLAAN KEUANGAN DAERAH - Setiawan, Achdiar Redy; Irianto, Gugus; Achsin, Mohammad (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Abstract: System-Driven (Un)Fraud: Actorâs Meaning of the âDark Sideâ ofÂ Local Government Financial Management. The purpose of this study is to uncover the actual practices of local government financial management in the smallest scope, namely SKPD (local government work units). This research focuses on the meaning of âthe dark sideâ(a reality which stands behind the formal procedures and documentation that are displayed) from the actors who are government apparatus. Hermeneutics Gadamerian was chosen asÂ the research methodology. Traces of